2020
DOI: 10.1038/s41598-020-59154-5
|View full text |Cite
|
Sign up to set email alerts
|

The novel application of cordycepin in maintaining stem cell pluripotency and increasing iPS cell generation efficiency

Abstract: Maintaining the pluripotency of either embryonic stem (eS) cells or induced pluripotent stem (ipS) cells is a fundamental part of stem cell research. in this study, we reported that cordycepin promoted the expression of pluripotency markers in eS and ipS cells. eS cells treated with cordycepin demonstratedtheir potential for generating embryoid bodies and differentiating into all three germ layers. The expression levels of phospho-Jak2, phospho-Stat3, integrin αV, and integrin β5 were increased after cordycepi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…However, concentrations above 10 µM showed the cytotoxic effect. Wang et al reported similar results in embryonic stem cells [ 14 ].…”
Section: Discussionsupporting
confidence: 55%
“…However, concentrations above 10 µM showed the cytotoxic effect. Wang et al reported similar results in embryonic stem cells [ 14 ].…”
Section: Discussionsupporting
confidence: 55%
“…We noted 45 papers claiming that the cytotoxic effect of cordycepin at bioactive concentrations was low. We noted the highest concentration which promoted cell survival or did not cause statistically significant cell death in these papers and determined the median and the range [28][29][30][32][33][34][35][36][37][38][39][40][41][42][43][44]69,70,80,95,98,102,105,106,117,142,145,164,184,240,270,301,315,317,[326][327][328][329][330][331][332][333][334][335][336].…”
Section: Cordycepin Concentrations and Cell Viability In Mammalian Tissue Culturementioning
confidence: 99%
“…The Janus tyrosine kinase 2 (JAK2)/signal transducer and activator of transcription 3 (STAT3) signaling plays a major role in leptin’s regulation of food intake [ 40 ]. Previous studies found that cordycepin treatment improved the phosphorylation of JAK2 and STAT3 protein which leads to reduce the food intake [ 36 , 49 , 72 ]. This is clearly that cordycepin could reduce the food intake via JAK2/STAT3 signaling pathway in DM mice.…”
Section: Discussionmentioning
confidence: 99%